Resilience and Servant Leadership as Predictors of Organizational Commitment in Generation Z Employees - Marhisar Simatupang; Rina Anindita; Winanti Siwi Respati; Liana Mailani (Universitas PGRI Yogyakarta, 2026)
High turnover intention among Generation Z employees remains a major challenge for organizations in Indonesia. Many young workers leave their jobs within the first two years due to better career opportunities, poor organizational culture fit, and difficulties in maintaining work–life balance. This condition emphasizes the importance of strengthening organizational commitment among young employees. This study aims to examine the direct influence of resilience and servant leadership on organizational commitment among Generation Z employees. The participants were 410 employees aged 18 to 29 years (M = 23.6, SD = 2.9), including 156 male employees (38.0%) and 254 female employees (62.0%). Organizational commitment was measured using the Organizational Commitment Scale developed by Allen and Meyer (1990), adapted for the Indonesian context. Resilience was assessed using the Resilience Scale by Reivich and Shatté (2002), while servant leadership was measured using the Servant Leadership Scale by Liden et al. (2008). All instruments demonstrated excellent reliability (Cronbach’s α > .90). The results show that both resilience and servant leadership have significant positive effects on organizational commitment. These findings highlight the importance of developing resilience and servant-oriented leadership as key strategies to enhance employee commitment and reduce turnover intention among Generation Z workers. Keywords: resilience, servant leadership, organizational commitment